Major Factors for the Persistent Folding of Hybrid α, β, γ-Hybrid Peptides Into Hairpins - Zhong, Yulong; Tang, Quan; Miller, Daniel P.; Zurek, Eva; Liu, Rui; Lu, Zhong-Lin; Gong, Bing (Frontiers in Chemistry, 2020)
Factors responsible for the persistent adoption of hairpin conformations by hybrid oligopeptides, each having a central β/α dipeptide segment flanked by aromatic γ-amino acid (γAr) residues, are probed. Our recent studies revealed that tetrapeptide 1 and 2, having central dipeptide segments consisting of β-alanine (β-Ala) and glycine (Gly), and L-β-homophenylalanine (L-β-homoPhe) and Gly residues, respectively, which are flanked by γAr residues, fold into well defined, expanded β-turns with doubly H-bonded γAr residues. Replacing the γAr residues of 1 and 2 with L-Val and L-Leu residues results in tetrapetides 1’ and 2’ that fail to fold into defined conformations, which confirms the decisive role played by the H-bonded γAr residues in promoting the folding of 1 and 2. Attaching L-Val and L-Leu residues to the termini of 1 affords hexapeptide 1a. With an additional H-bond between its L-Val and L-Leu residues, peptide 1a folds into a hairpin with stability greater than that of 1, indicating that the expanded β-turn can nucleate and stabilize β-hairpin with longer β-strands. Attaching L-Val and L-Leu residues to the termini of 2 affords hexapeptide 2a. Substituting the L-β-homoPhe residue of 2a with a D-β-homoPhe residue gives hexapeptide 2b. Surprisingly, hexapeptide 2a folds into a hairpin showing similar stability as those of tetrapeptides 1 and 2. Hexapeptide 2b, with its combination of a D-β-homoPhe residue and the L-Val/L-Leu pair, fold into a hairpin that is significantly more stable than the other hybrid peptides, demonstrating that a combination of hetero-chirality between the β-amino acid residue of the dipeptide loop and the α-amino acid residues of the β-strands enhances the stability of the resultant β-hairpin.